Exact Solution for Forced Convection Gaseous Slip Flow in Corrugated Microtubes - Siginer, D (Elsevier Ltd, 2017)
Forced convection heat transfer in fully developed gaseous laminar slip flow in transversally corrugated micropipes is investigated for first-order slip boundary conditions on the wall. The governing equations subject to first-order slip boundary conditions are solved analytically by means of the epitrochoid conformal mapping. Closed-form exact expressions are obtained for the velocity and temperature fields for the first time. The effects of the corrugation on the pressure drop and heat transfer rate are discussed in detail. Exact results obtained in this paper are compared with the recent approximate analytical solution in the literature, Sadeghi et al. (2011) [1]. © 2017 Elsevier Ltd